Ethnomedicinal Plants Used by Baiga Tribe of District Dindori, Madhya Pradesh - Ahirwar, Ramesh Kumar (Indian Forester, 2018)
Present paper reports the ethnomedicinal uses of 68 plants belonging to 60 genera and 43 families used for curing various diseases by the Baiga tribes of district Dindori, Madhya Pradesh. The botanical names, local names and family names of these plants, used dosages, mode of drug preparation and administration are prescribed.